Dialektika Teori Kontrak Sosial dan Pancasila dalam Penguatan Peran Civil Society di Indonesia - Akhirul Aminulloh; Abd. Mu'id Aris Shofa; Firman Firdausi; Emei Dwinanarhati Setiamandani (Yayasan Lentera Avanya Nagari, 2026)
Pancasila as the Staatsfundamentalnorm faces substantive challenges in the era of disruption, characterized by the waning understanding of national values among the younger generation and growing public mistrust toward the government. This study aims to analyze the role of civil society in internalizing Pancasila values and shaping civic character. Utilizing a normative juridical method with a legal philosophy and statutory approach, this research compares the social contract theories of John Locke and Jean-Jacques Rousseau within the framework of Pancasila. The results show that Indonesian civil society continues to uphold the noble virtues of Pancasila through the manifestation of social solidarity (the